Acute and sub-chronic toxicity studies of the ethanol extract of Erythrina fusca Lour. fruit via oral administration in mice - Phuong-Nhung, Tran Thi; Quoc, Le Pham Tan (Acta Biologica Szegediensis, 2023)
Erythrina fusca Lour. is a medicinal plant traditionally used in herbal medicine; however, there are no records of toxicity associated with the ethanol extract of E. fusca fruit (EtEF). The objective of this study was to assess the safety of EtEF through toxicity testing. Four groups of Swiss albino mice were employed, including a control group and three groups administered EtEF at doses of 1000, 3000, and 5000 mg/kg (single dose) and 100, 300, and 500 mg/kg (administered repeatedly for 90 days). Various parameters, including body weight, food and water consumption, hematological and biochemical parameters, relative organ weight, urine composition, and histopathology, were evaluated. No significant differences were observed in the tested groups compared to the control group, and there was no evidence of morphological or histopathological damage in the organs of mice treated with EtEF. This study affirms the safety of EtEF and establishes a foundation for further investigations into its utilization in traditional medicine.